An improved weighted average simulation approach for solving reliability-based analysis and design optimization problems. (May 2016) - Okasha, Nader M.
Highlights: I propose a modification to the weighted average simulation method (WASM). The probability of failure rapidly converges to the final result. The modification allows the computation of the reliability with a small number of performance function evaluations. I also propose an improved WASM approach for efficiently conducting the reliability-based design optimization problems. The same results as the original WASM are obtained with only a fraction of the computational cost required. Abstract: The weighted average simulation technique is one of the newest techniques that showed promising capabilities in solving structural reliability problems. In this paper, a modification to the weighted average simulation method is proposed, which allows the computation of the reliability with a small number of performance function evaluations. In addition, an approach for conducting reliability-based design optimization problems by introducing an additional improvement to the weighted average simulation method is proposed. This improvement significantly reduces the number of performance function evaluations needed in the process without sacrificing the accuracy of the results. It was found that the proposed approach can obtain the same results as the original weighted average simulation method with only a fraction of the computational cost required.